PENGARUH SIKAP, NORMA SUBJEKTIF DAN KONTROL PERILAKU YANG DIRASAKAN TERHADAP NIAT MEMBELI (Studi Kasus BreadTalk) - Sunarto, Novia (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2022)
This research aims to determine the effect of attitude, subjective norms and perceived behavior control on buying intentions in the region of BreadTalk customers at West Jakarta. This type of research is descriptive research with quantitative approaches, as for the data collection technique is done with a technique method of causality with the selection of the sample using the method of incidental sampling. Sample as many as 100 of the respondents which is active student customers BreadTalk. The data analysis used was multiple linear regression analysis with SPSS statistics software tool version 23. The results of this research show that the attitudes variable, subjective norms variable and perceived behavior control has a positive and significant effect against the intention of buying customers BreadTalk. But in a partial attitude variable has more positive and significant effect to the intention of buying customers BreadTalk, then follow by subjective norms variable. In contrast to the perceived behavior control, partially this variable has not been influential positively and significantly to the intention of buying customers BreadTalk.